2008
DOI: 10.1186/1745-6673-3-31
|View full text |Cite
|
Sign up to set email alerts
|

Surgical smoke and ultrafine particles

Abstract: Background: Electrocautery, laser tissue ablation, and ultrasonic scalpel tissue dissection all generate a 'surgical smoke' containing ultrafine (<100 nm) and accumulation mode particles (< 1 μm). Epidemiological and toxicological studies have shown that exposure to particulate air

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
133
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 32 publications
5
133
0
5
Order By: Relevance
“…The size of such particles closely depends on the particular instruments used. Indeed, various investigations have revealed that the electrocautery releases the smallest particles, with a mean aerodynamic size of 0.07 µm, whereas laser tissue coagulation produces larger particles (0.31 µm) and the largest particles are generated by the ultrasonic scalpel (0.35–6.5 µm) [12].…”
Section: Discussionmentioning
confidence: 99%
“…The size of such particles closely depends on the particular instruments used. Indeed, various investigations have revealed that the electrocautery releases the smallest particles, with a mean aerodynamic size of 0.07 µm, whereas laser tissue coagulation produces larger particles (0.31 µm) and the largest particles are generated by the ultrasonic scalpel (0.35–6.5 µm) [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the tasks performed during the finishing stages of tunnel construction will be similar to the work carried out by tunnel rehabilitation workers. Exposure to ultrafine particles is documented in other industries and processes relevant to tunnel construction or rehabilitation, including welding,6–8 the rubber manufacturing industry,9 asphalt work,10 paving and related road construction operations,11 industrial plants,12 as well as other types of exposure such as cooking13–16 and surgical smoke exposure 17 18…”
Section: Introductionmentioning
confidence: 99%
“…Personal exposure, measured by sampling in the breathing zone, has been measured only in a few studies. These studies concern exposure to cooking fumes,13 16 exposure levels for airport employees,30 surgical smoke exposure,17 18 paving and road construction workers11 and welding 6 34. An overview of the results is presented in table 2.…”
Section: Introductionmentioning
confidence: 99%
“…Since the peritoneal cavity is inflated with carbon dioxide, surgical smoke, an unwanted by product of coagulation, is formed in an oxygen-free atmosphere [1]. As a result of pyrolysis a number of chemical substances, which are known to have a toxic effect on the human body, are formed.…”
Section: Introductionmentioning
confidence: 99%